Fodder potential of triticale (× Tritisecale Wittmack) genotypes in Nepal: Evaluation of biomass and seed productivity - Ghimire, Ram Prasad; Russell, Adrian; Pariyar, Dinesh; Hampton, John; Armstrong, Keith; Shrestha, Kishor Kumar; Rolston, M. Phil; Stevens, E John; Amgain, Rita (Nepal Agriculture Research Journal, 2025)
Triticale (× Triticosecale Wittmack) is a hybrid cereal combining the high grain quality and yield potential of wheat with the adaptability and resilience of rye. This study evaluates the performance of three triticale cultivars (Bolt, Wintermax and Crackerjack) and recommended cultivars of wheat and oat for winter fodder and seed production across four ecological regions in Nepal. A randomized complete block design (RCBD) with three replications was used to assess fodder yield and quality, and seed production over two consecutive years. Fodder yield varied significantly (p